Modeling the system dynamics of irrigators' resilience to climate change in a glacier-influenced watershed. Issue 12 (10th September 2021) - Ross, Alexander Reid; Chang, Heejun
ABSTRACT: Glacier-dependent streams and irrigation systems in the Hood River Watershed (HRW) are particularly vulnerable to climate change, as glaciers retreat and snowpack declines. We developed a system dynamics model designed to test and improve resilience of the HRW's socio-hydrological system under Coupled Modeling Intercomparison Project 5 (CMIP5) climate change scenarios and irrigation infrastructure improvement, water banking, and water conservation. We hypothesized irrigators' potential strategies would increase adaptive capacity by ensuring sufficient water resources for irrigation and minimum streamflow for fish habitat. Our model suggested predicted temperature increases will cause a lengthening of the dry season, causing streamflow declines, but adaptive measures have the potential to increase the capacity of the socio-hydrological system to "bounce back" from strains on streamflow given collective cooperation and the acceptance of agriculture–ecology tradeoffs. Hence, we found that system dynamics models offer useful tools for simulating localized potential impacts of climate change and developing possible solutions to improve resilience.